Depression, sexual behavior, and HIV treatment outcomes among transgender women, cisgender women and men who have sex with men living with HIV in Brazil and Thailand: a short report - Tonia C. Poteat (2020)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. One in five transgender women (TW) are living with HIV, yet little has been published about their health outcomes. We analyzed data from TW (n = 37), cisgender women (CW, n = 165), and cisgender men who have sex with men (MSM, n = 151) in Thailand and Brazil. We hypothesized: (1) TW will have higher odds of depressive symptoms, lower odds of condom use and greater odds of a detectable viral load compared to MSM and CW; and (2) TW will have lower odds of condom use and higher odds of detectable viral load. We found that TW had higher odds of depression (OR 2.2, 95%CI: 1.0, 4.8, p = 0.04) and were less likely than MSM (22% v. 42%, p = 0.01) to use condoms with partners of unknown serostatus. In multivariable models, TW had lower odds than MSM of using condoms with partners with unknown serostatus (OR 0.38, 95%CI: 0.15, 0.90) and CW had lower odds than MSM of using condoms with HIV-negative partners (0.60 [0.38, 0.95], p = 0.029). We found no significant differences in detectable viral load. Disaggregating data by gender is important to understand factors that contribute to viral suppression and HIV transmission risk among people living with HIV.